Design E-learning Environment Based on Learning Platforms and its impact on Achievement and Developing Digital Citizenship Skills in the Computer course for Middle school students - Alhejaili, Manal Rabeh (Journal of Educational and Psychological Sciences, 2023)
The aim of the current research is to find out the effect of designing a cartoon learning environment based on learning platforms on achievement and the development of self-learning skills in mathematics for first year secondary school students. The research used the experimental method; To achieve this goal, an electronic learning environment was designed based on the Microsoft Teams learning platform.” An achievement test and a scale for self-learning skills were prepared, and the research sample included (50) female students from the first year of secondary school in the Wadi Al-Far’a sector of the Madinah Region, the Education Office of West Al-Madinah Al-Munawwarah, The research sample was divided into two groups: The first was an experimental group of (25) students who studied using an electronic learning environment based on the “Microsoft Teams learning platform”, and the other was a control group consisting of (25) students who studied using an electronic learning environment based on the “My School” learning platform, and statistical methods were used, Pearson correlation coefficient. And the Shapiro test and the t-value test, and the results of the research resulted in a statistically significant difference at the level (0.05) between the mean scores of the students of the experimental and control groups in the post-application of the achievement test in favor of the experimental group, and there was no statistically significant difference at Level (0.05) between the mean scores of the students of the experimental and control groups in the post application of the self-learning skills scale.